ANALISIS PENDAPATAN USAHA GULA AREN DI DESA GANTARANG KABUPATEN SINJAI SULAWESI SELATAN - Sri wahyuni Haris; Makkarennu Makkarennu; Ridwan Ridwan (PERENNIAL, 2020)
Non-timber forest products (NTFPs) has a significant role both from the economic aspect as well as the ecological and socio-cultural aspects. Aren (Arrenga pinnata Merr) is one of NTFPs that has high economic value so that it is managed and cultivated by the community, especially for those who live around the forest. However, the management of the palm sugar business is still simple and limited to household businesses for the fulfillment of daily life. This study aims to calculate the income earned by sugar palm processing farmers, especially in one village in Sinjai Regency, South Sulawesi. The data collection method was carried out through direct observation and interviews with 30 respondents for sugar block products and 5 respondents for palm sugar. The data analysis using net income including analysis of total costs and analysis of total revenues on sugar block and palm sugar. The results showed that this palm sugar business contributed to the income of the community, especially palm sugar processing farmers with an average income of Rp.10,864,500 per year for sugar block and Rp.7,555,200 for palm sugar. Palm farmers in Gantarang Village who produce sugar block have a higher income than those producing palm sugar because farmers generally produce sugar block. This is partly due to the amount of production produced, costs incurred, revenues and skills possessed by palm sugar processors.